Community clinics: an effective avenue for delivering primary healthcare services to urban vulnerable population under NUHM during COVID-19 era and beyond - Basa, Sudipta; Gupta, Basab (International Journal Of Community Medicine And Public Health, 2021)
The urban population in our country is increasing rapidly and represents the 2-3-4-5 syndrome. It is estimated that by 2031, there would be about 600 million people living in urban India. The health of the urban poor is considerably worse off than the urban middle and high income groups and is maybe even worse than the rural population. Even after more than 40 years of Alma Ata’s declaration the main focus on provision of Primary Healthcare based on principles of social inclusion, equity and comprehensiveness has lost some attention in-between. With the abrupt and sudden outbreak of COVID-19, has put the health system into crisis all over the country especially in urban areas. Lakhs of vulnerable population in slum areas had to suffer in absence of provision of basic primary health care (PHC) services during the lockdown period. In this article we present the need of community clinics under NUHM, an effective avenue for delivering PHC services for vulnerable population in this ongoing COVID-19 pandemic era and beyond.